2017
DOI: 10.1088/1361-6404/aa8baa
|View full text |Cite
|
Sign up to set email alerts
|

Application of peer instruction in the laboratory task of measuring the effective mass of a spring

Abstract: Peer instruction (PI) is an effective interactive approach to teaching and learning that has principally been used to modify the experience of learning in traditional physics lecture settings. This article further illustrates how the concept of PI can be effectively applied in the physics student laboratory setting. The setting used is a laboratory task that calls for the measurement of the effective mass of the spring of a Jolly balance. Through PI the students gain a better understanding of what is meant by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Peer response and writing process designs have been used in science education, see e.g. references [51] and [52], and peer instruction is studied in the PER-context [53,54], but we believe we offer a closer analysis of its impact and a transferable rationale for the design.…”
Section: Introductionmentioning
confidence: 99%
“…Peer response and writing process designs have been used in science education, see e.g. references [51] and [52], and peer instruction is studied in the PER-context [53,54], but we believe we offer a closer analysis of its impact and a transferable rationale for the design.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature reviews have shown that PI is an effective teaching method (Vickrey et al 2015, Müller et al 2017. Although most investigations report the use of PI as an alternative to traditional lectures, it was also proven to be effective in laboratory classes (Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%